2017
DOI: 10.1016/j.neuroimage.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reduction of BOLD modulation to cognitive difficulty predicts poorer task accuracy and poorer fluid reasoning ability

Abstract: Aging is associated with reduced resources needed to perform difficult cognitive tasks, but the neural underpinnings are not well understood, especially as there is scant evidence linking functional brain differences to aging cognition. Therefore, the current study examined modulation of fMRI activation from easier to harder spatial distance judgments across a large lifespan sample (N=161; ages 20–94) to identify when in the lifespan modulation to difficulty begins to show deficits and if age-related modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
93
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 64 publications
18
93
2
Order By: Relevance
“…We have recently shown that increased coupling of these networks, as predicted by the DECHA is associated with reduced fluid intelligence and increased reliance on semantic or crystalized knowledge in older adulthood [126]. Recent evidence both from cross-sectional [96] and longitudinal [127] investigations provide support for this hypothesis and provide further evidence that these changes in network interactivity can predict individual differences in cognitive functioning. Taken together these network-based accounts of functional brain aging point to network neuroscience as an important new frontier in neurocognitive aging research.…”
Section: Changes In Functional Brain Networkmentioning
confidence: 79%
See 2 more Smart Citations
“…We have recently shown that increased coupling of these networks, as predicted by the DECHA is associated with reduced fluid intelligence and increased reliance on semantic or crystalized knowledge in older adulthood [126]. Recent evidence both from cross-sectional [96] and longitudinal [127] investigations provide support for this hypothesis and provide further evidence that these changes in network interactivity can predict individual differences in cognitive functioning. Taken together these network-based accounts of functional brain aging point to network neuroscience as an important new frontier in neurocognitive aging research.…”
Section: Changes In Functional Brain Networkmentioning
confidence: 79%
“…Finally, substitution reflects activation of entirely novel neural networks in older relative to younger adults, perhaps signaling strategy differences or functional reorganization [e.g. 96,97].…”
Section: Domain-general Changes: Neural Dedifferentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural changes in APOE protein impact its ability to bind with lipids and ␤-amyloid and to reduce its functional ability to maintain neuronal health (Frieden and Garai, 2012;Liu et al, 2013). Indeed, 4-positive (4ϩ) individuals are more likely to accumulate extracellular ␤-amyloid (A␤) protein, as the APOE4 isoform reduces A␤ clearance and increases A␤ aggregation (Verghese et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 4-positive (4ϩ) individuals are more likely to accumulate extracellular ␤-amyloid (A␤) protein, as the APOE4 isoform reduces A␤ clearance and increases A␤ aggregation (Verghese et al, 2011). Without adequate clearance, ␤-amyloid can form oligomers and plaque, which are thought to be neuro-toxic to neurons (Liu et al, 2013;Scheltens et al, 2016). Thus, APOE4 carriers are likely to show reduced efficiency in neural function, and fMRI evidence suggests that differences in taskrelated brain function are apparent in even younger adults Dennis et al, 2010;Matura et al, 2014;Suri et al, 2015), far preceding the development of AD.…”
Section: Introductionmentioning
confidence: 99%